Industrial Modernism and the Hegelian Dialectic in Winslow Homer - Griffith, Trevor (Labyrinth, 2021)
This paper looks at the themes of nature, humanity, and military and industrial development in the nineteenth century American painter Winslow Homer through the lens of the Hegelian theory of art. Robert Pippin's After the Beautiful (2015) has recently put the Hegelian framework to very fruitful use in understanding pictorial modernism. This study of Homer follows a similar approach but argues that Homer's canvases represent a development in the modern spirt which, in many ways, goes beyond the canvases of Manet – a very tight modernist contemporary of Homer's. Homer communicates a presentment of the immense and, in certain profound respects, horrifying power of humanity's growing industrialization. I trace the development of this idea over the course of his career, from this early Civil War canvases to his final seascapes and argue that an understanding of Homer's work is important for understanding the modern spirit of the nineteenth and twentieth centuries.